Towards more realistic conceptualisations of foreign operation modes - Benito, Gabriel RG; Petersen, Bent; Welch, Lawrence S (Journal of International Business Studies, 2009)
We address a long-standing discrepancy between theory and practice regarding how firms choose, use, and modify their modes of operation in foreign markets. Theory typically treats foreign operation modes as choices between well-specified, discrete alternatives. Observation of business practice reveals a “messier” reality. We commonly observe mode packages, within-mode adjustments and mode role changes, yet by and large these aspects of international business development have been relatively ignored in the literature, and in theoretical and empirical research. We propose richer and more realistic conceptualisations of foreign operation modes, and look at their implications for theory and practice.